Strengthening Democratic Values and Tolerance through a Social Studies Learning Model Based on Contemporary Social Issues - Dewi Kartika Sari; Arif Rahman Hakim; Ridwan Hidayat (Journal of Social Studies Education, 2026)
The increasing complexity of contemporary social issues, including intolerance, social polarization, misinformation, discrimination, and identity-based conflicts, highlights the need for educational approaches that strengthen democratic values and tolerance among students. This study aimed to develop and evaluate the effectiveness of a Contemporary Social Issues-Based Social Studies Learning Model in strengthening democratic values and tolerance among junior high school students. The study employed a Research and Development (R&D) approach using the ADDIE framework, consisting of analysis, design, development, implementation, and evaluation stages. The effectiveness of the developed model was examined through a quasi-experimental design involving experimental and control groups. Data were collected through observations, questionnaires, interviews, and documentation and were analyzed using both quantitative and qualitative techniques. The findings revealed that the developed learning model achieved a very high level of validity based on expert evaluations. Furthermore, students who participated in the model demonstrated significantly higher improvements in democratic values and tolerance compared to students who received conventional instruction. The learning process encouraged active participation, democratic dialogue, critical inquiry, collaborative problem-solving, and reflective thinking through the exploration of authentic contemporary social issues. Students also reported highly positive responses toward the learning experience, particularly regarding learning relevance, participation opportunities, and collaborative activities. The study concludes that the Contemporary Social Issues-Based Social Studies Learning Model is an effective instructional innovation for promoting democratic citizenship and tolerance. The model contributes both theoretically and practically to the advancement of Social Studies education by providing a contextual and participatory framework for preparing students to become democratic, responsible, and tolerant citizens in diverse societies.